2007
DOI: 10.2111/05-218r3.1
|View full text |Cite
|
Sign up to set email alerts
|

Initial Effects of Brush Cutting and Shoot Removal on Willow Browse Quality

Abstract: We examined the initial effects of brush cutting (removal of all aboveground biomass), as well as clipping (removal of current annual shoots) and ungulate browsing (collectively referred to as shoot removal) on the morphology and nutrient quality of Scouler's willow (Salix scouleriana J. Barratt ex Hook.) for ungulates on sites 2 and 4 years after brush cutting. We specifically assessed changes in the biomass, tannin content, digestible energy, and digestible protein of shoots from brush-cut willows relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Although some other studies have shown a decrease in shoots size in response to winter browsing [7, 33], most previous studies have shown increases in shoot size [9, 10, 23, 26, 32, 34], or needle size in pine [24], which we did not measure. The discrepancy may have arisen because we studied multiple species in natural forest stands with low productivity and recurring browsing, whilst most other studies focused on only one species in one season, and, in some cases, were simulated browsing experiments.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Although some other studies have shown a decrease in shoots size in response to winter browsing [7, 33], most previous studies have shown increases in shoot size [9, 10, 23, 26, 32, 34], or needle size in pine [24], which we did not measure. The discrepancy may have arisen because we studied multiple species in natural forest stands with low productivity and recurring browsing, whilst most other studies focused on only one species in one season, and, in some cases, were simulated browsing experiments.…”
Section: Discussionmentioning
confidence: 77%
“…However, the observed preference for trees with high accumulated browsing could be caused by increased nutrient concentration or reduced concentration of plant secondary compounds. Previous studies have found that the carbon demands of regrowth reduces production of secondary defense compounds in previously browsed trees [7, 16, 28, 34], while increased nutrient concentration can occur because of the reduced number of meristems [18, 19]. Moose selection of winter browse is known to be negatively related to the concentration of specific phenolics in Salix phylicifolia , and concentrations were lower in previously browsed shoots [63].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences between biomass regrowth for the Bio-Baler and hand-prune treatments were statistically significant for S. discolor but not S. eriocpehala or S. petiolaris. Other studies have shown that brush cutting willow resulted in production of large stems and vigorous vegetative regeneration [21]. The production of large stems is a growth strategy employed by several Salix species [20] especially where competition for canopy occupancy is intense [22], which is typical of the moist, nutrient-rich areas on the periphery of wetlands.…”
Section: Stem Regrowth After Mechanical Harvestmentioning
confidence: 99%